‘China Central Television’s Globalisation Strategy and Its Impact on the World Communication Order’ - Yan Wu (Modern Communication, 2008)
Media policy governing international communication is constantly integrated into national development strategies. The structural transformation of China’s international television broadcasting highlights the significant impact of state on communication issues in the global context. In the past three decades, China has enjoyed remarkable development and media have been designated the role of facilitating the country’s economic growth and opening up to the world. In this paper, we examine the historical development of China Central Television International Service (CCTVIS), scrutinise the relationship between state and media, and evaluate the influence of CCTVIS on contemporary world information and communication order.